OCEB certification guide business process management, fundamental level - Weilkiens, Tim; Weiss, Christian; Grass, Andrea R.; Duggen, Kim Nena (Morgan Kaufmann, 2016)
OCEB 2 Certification Guide, Second Edition has been updated to cover the new version 2 of the BPMN standard and delivers expert insight into BPM from one of the developers of the OCEB Fundamental exam, offering full coverage of the fundamental exam material for both the business and technical tracks to further certification. The first study guide prepares candidates to take--and pass--the OCEB Fundamental exam, explaining and building on basic concepts, focusing on key areas, and testing knowledge of all critical topics with sample questions and detailed answers. Suitable for practitioners, and those newer to the field, this book provides a solid grounding in business process management based on the authors' own extensive BPM consulting experiences. Completely updated, with the latest material needed to pass the OCEB-2 and BPMN Certification Includes sample test questions in each chapter, with answers in the appendix Expert authors provide a solid overview of business process management (BPM).